Automated Reasoning with Analytic Tableaux and Related Methods 18th International Conference, TABLEAUX 2009, Oslo, Norway, July 6-10, 2009. Proceedings - Giese, Martin; Waaler, Arild; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This book constitutes the refereed proceedings of the 18th International Conference on Automated Reasoning with Analytic Tableaux and Related Methods, TABLEAUX 2009, held in Oslo, Norway, in July 2009. The 21 revised research papers presented together with 1 system description and 2 invited talks were carefully reviewed and selected from 44 submissions. The papers cover many topics in the wide range of applications of tableaux and related methods in areas such as hardware and software verfications, semantic technologies, and knowledge engineering.
Presenting Constraints -- On the Use of Automata for Deciding Linear Arithmetic -- Comparative Concept Similarity over Minspaces: Axiomatisation and Tableaux Calculus -- A Schemata Calculus for Propositional Logic -- Tableaux and Model Checking for Memory Logics -- Canonical Constructive Systems -- A Novel Architecture for Situation Awareness Systems -- On the Proof Theory of Regular Fixed Points -- Decidability for Priorean Linear Time Using a Fixed-Point Labelled Calculus -- A Tableau-Based System for Spatial Reasoning about Directional Relations -- Terminating Tableaux for the Basic Fragment of Simple Type Theory -- Modular Sequent Systems for Modal Logic -- Abduction and Consequence Generation in a Support System for the Design of Logical Multiple-Choice Questions -- Goal-Directed Invariant Synthesis for Model Checking Modulo Theories -- Taming Displayed Tense Logics Using Nested Sequents with Deep Inference -- Sound Global State Caching for ALC with Inverse Roles -- A Tableau System for the Modal ?-Calculus -- Terminating Tableaux for Graded Hybrid Logic with Global Modalities and Role Hierarchies -- Prime Implicate Tries -- Proof Systems for a Gödel Modal Logic -- Generic Modal Cut Elimination Applied to Conditional Logics -- Proof Search and Counter-Model Construction for Bi-intuitionistic Propositional Logic with Labelled Sequents -- Automated Synthesis of Tableau Calculi -- Tableaux for Projection Computation and Knowledge Compilation.
Keywords: Computer science; Computer programming; Software engineering; Mathematical logic; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Mathematical Logic and Formal Languages; Programming Techniques; Software Engineering; Electronic books